Peran Recovery Kemualafan Yayasan Mualaf Center Indonesia Kota Pematang Siantar - Muhaimin, Rizky Akbar; Harahap, Indra; Siregar, Husna Sari (Kamaya: Jurnal Ilmu Agama, 2024)
The issues of this research are based on the lack of guidance for converts, who are new to Islam and are still vulnerable in their faith. The purpose of this research is to find out the extent of the development of converts to Islam and to see the guidance implemented by the Mualaf Center Foundation in implementing their programmes. This research uses a qualitative method with a fielld relselarch. Data were collected through direct observation and in-depth interviews with converts who participated in the coaching programme at the Indonesian Mualaf Center Foundation in Pematang Siantar City. The purposive sampling technique was used to select informants who are relevant and have significant experience in the coaching programme. The data obtained were then analysed using thematic analysis to identify patterns and main themes that emerged related to the effectiveness of the converts' coaching program. The results of this study indicate that the Indonesian Mualaf Center Foundation in Pematang Siantar City has successfully fostered converts through various structured programmes. The converts reported improved ability to read the Quran and a better understanding of the teachings of Islam. The coaching programme includes religious classes, Quran reading training, and social support. The foundation's success is also evident from the high level of satisfaction among converts, who feel more integrated and supported within the Muslim community. Challenges faced include the need for more resources and trained teaching personnel.